Structure-inspired design of a sphingolipid mimic sphingosine-1-phosphate receptor agonist from a naturally occurring sphingomyelin synthase inhibitor. Issue 90 (26th October 2018) - Swamy, Mahadeva M. M.; Murai, Yuta; Ohno, Yusuke; Jojima, Keisuke; Kihara, Akio; Mitsutake, Susumu; Igarashi, Yasuyuki; Yu, Jian; Yao, Min; Suga, Yoshiko; Anetai, Masaki; Monde, Kenji
Abstract : A monophosphate derivative of ginkgolic acid binds to sphingosine 1-phosphate (S1P) receptors to perform similar functions to the lipid mediator S1P. Abstract : Ginkgolic acid obtained as a sphingomyelin synthase inhibitor from a plant extract library inspired the concept of sphingolipid mimics. Ginkgolic acid-derived N -acyl anilines and ginkgolic acid 2-phosphate (GA2P) respectively mimic ceramide and sphingosine 1-phosphate (S1P) in structure and function. The GA2P-induced phosphorylation of ERK and internalization of S1P receptor 1 (S1P1 ) indicated potent agonist activity. Docking studies revealed that GA2P adopts a similar binding conformation to the bound ligand ML5, which is a strong antagonist of S1P1 .